To reduce pain to heel prick in newborn: comparison with six lancet devices - G. Ballardini; A. Spruzzola; L. Boneschi; R. Visentin; L. Boscardini; M. Barbaglia; A. Guala (PAGEPress Publications, 2012)
Heel prick is an usual method performed to get a blood sample for newborn screening. Its wide use justifies the effort in reducing the pain as much as possible and some simple steps, including the use of spring heelsticks, are recommended by national and international guide- lines. But not all the heelsticks cause the same pain and allow to get enough blood for the screening. The aim of this work was to test six automatic heelstick devices with regard to the pain in heel prick measured with NIPS scale and, at the same time, to value their effectiveness in getting a blood sample suitable for filter paper for newborn screening. The following devices were assessed: Amnes Minilet Lancets, Wuxi Xinda Ltd, Exxe Safe Blade, Lifescan Stik Johnson & Johnson, One Touch Ultra Soft, Accu-Chek Safe T Pro Plus. The device Exxe Safe Blade statistically differs from all others: it is the least painful and it doesn't need any prick repetition.